Who's afraid of China's high-tech challenge? - Guy De Jonquières (European Centre for International Political Economy (ECIPE), 2013)
Over the last 30 years, the speed and scale of China's economic rise have stunned the world. Now its government has mapped out bold plans for the next phase of the nation's development: transforming it into an innovation powerhouse that occupies a leading, and ultimately dominant, global position in a range of science-based industries of the future.China's ambitions and the government's central role in formulating strategies and mobilising resources for fulfilling them have evoked mixed responses elsewhere. Some foreign policymakers and businesses complain that the country's dirigiste approach and subsidies distort competition and flout trade rules. Others, in contrast, argue that other countries should be inspired by China's example to embrace more active industrial policies aimed at promoting successful high-technology champions. This paper examines China's policies and its current level of industrial development. It finds that many of its efforts so far to stimulate innovation are less impressive than they seem and questions whether the country's ambitions are attainable. It concludes that, while there is a role for the right kind of industrial policy, China's version is deeply flawed and that policy makers elsewhere would be unwise to try to emulate it.
Keywords: 330; Technologiepolitik; Hochtechnologie; China